Developing K-Quiz Android Application of Descriptive Text English Listening Skill for Culinary Art Students: A Research and Development Study - Dyah Fantina; Supriyono; Sutanti Nita (JOSAR (Journal of Students Academic Research), 2026)
The objective of this research is to develop "K-Quiz," an Android-based application designed as an effective instructional media to improve the English listening skills of tenth-grade Culinary Art students at SMK Negeri 3 Blitar. This study addresses the specific challenges in vocational education, particularly the lack of interactive media that integrates culinary-themed descriptive texts with mobile technology. The methodology employed is Research and Development (R&D), following the systematic ADDIE model which consists of five integrated phases: Analysis, Design, Development, Implementation, and Evaluation. In the analysis phase, pedagogical observations and interviews revealed that students struggled with auditory comprehension due to the use of conventional, non-vocational learning materials. During the development phase, the "K-Quiz" application was constructed using an Android platform and underwent rigorous validation. The results of the material expert validation reached 86.6%, while the media expert validation achieved a score of 88.5%, placing the product in the "Highly Valid" category. In the implementation phase, a perception test conducted with tenth-grade culinary students yielded an average score of 92%, indicating that the application is highly practical and engaging for classroom use. The study concludes that the K-Quiz application effectively bridges the gap between general English theory and professional vocational requirements. It provides a flexible learning environment that enhances students' motivation and mastery of descriptive oral information in a culinary context.